Distributed Generation Integration to Grid using Multi-Level CHB Inverter - Velishala Ramu; P. Satish Kumar; G. N Sreenivas (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Environmental conditions, electrical modeling and developments in industries led to new power generation epoch where fat section of power required for load section is fed through extensive induction of distributed resources generally known as distributed generation [DG]. Distributed generation reduces the risk of environmental pollution and distance criterion posed from conventional power generation. This paper presents grid integration scheme of distributed generation using five-level cascaded H-Bridge (CHB) inverter. Reference currents used to produce pulses for switches in CHB are generated using a simple control strategy. Performance of the system was evaluated when only active power is fed from distributed generation to grid and also when both active and reactive powers were fed to grid from distributed generation. Proposed system was developed using MATLAB/SIMULINK software and results are presented.